Implementation of the Stunting Handling Policy in Sumedang Regency, West Java Province - Rosana Gitasavitri; Dahyar Daraba; Andi Azikin; Andi Masrich (Sean Institute, 2024)
This thesis discusses the implementation of the Stunting Management Policy in Sumedang Regency. Sumedang Regency is the district with the highest prevalence in West Java Province with a stunting prevalence rate of 27.6% (Indonesian Toddler Nutrition Case Study 2022). The aim of this research is to analyze how the policies that have been implemented are implemented and what factors influence them as well as efforts to optimize the implementation of stunting management policies in Sumedang Regency. The theory used to measure the success of stunting management policies in Sumedang Regency in this thesis is the conception described by Hamdi (2014) that the success of a policy is largely determined by the dimensions that influence the implementation of a policy, namely: 1) Productivity; 2) Linearity; and 3) Efficiency. The data obtained was analyzed using descriptive research methods with a qualitative approach, with data collection techniques namely observation, interviews and documentation and data analysis techniques namely data reduction, data presentation and decision making. The results of the research show that implementation has been effective, marked by various regulations issued by the Regional Government, which is proof that the government is very concerned about the stunting problem. The determining factor is cooperation to ensure that resources, both human and other resources, are sufficient. The efforts that have been made include innovations such as the Joint Movement Against Stunting with the aim of carrying out real action in the field together by all stakeholders including government, business, academics and the community so that families at risk of stunting receive program intervention according to their needs.